Effects of Empagliflozin on Gut Microbiota in Heart Failure with a Preserved Ejection Fraction: The Design of a Pragmatic Randomized, Open-Label Controlled Trial (EMPAGUM) - Guan XQ; Wang CH; Cheng P; Fu LY; Wu QJ; Cheng G; Guan L; Sun ZJ (Dove Medical Press, 2023)
Xue-Qing Guan,1 Chuan-He Wang,1 Peng Cheng,1 Ling-Yu Fu,2 Qi-Jun Wu,3- 5 Gong Cheng,1 Lin Guan,1 Zhi-Jun Sun1 1Department of Cardiology, Shengjing Hospital of China Medical University, Shenyang, 110021, People's Republic of China; 2Department of Clinical Epidemiology and Evidence-Based Medicine, The First Affiliated Hospital, China Medical University, Shenyang, 110021, People's Republic of China; 3Department of Clinical Epidemiology, Shengjing Hospital of China Medical University, Shenyang, 110021, People's Republic of China; 4Department of Obstetrics and Gynecology, Shengjing Hospital of China Medical University, Shenyang, 110021, People's Republic of China; 5Clinical Research Center, Shengjing Hospital of China Medical University, Shenyang, 110021, People's Republic of ChinaCorrespondence: Zhi-Jun Sun, Department of Cardiology, Shengjing Hospital of China Medical University, No. 39 of Huaxiang Road, Tiexi District, Shenyang, 110021, People's Republic of China, Tel +86 02496615, Email sunzhijunszj8@126.comAbstract: Although empagliflozin has been recommended for individuals with heart failure, its effects on heart failure with preserved ejection fraction (HFpEF) remain uncertain from a physiopathological standpoint. The metabolites produced by gut microbiota have been shown to have a crucial role in the development of heart failure. Sodium-glucose cotransporter-2 inhibitors (SGLT2) have been shown to change the make-up of the gut microbiota in rodent studies. There is mixed evidence from similar studies investigating whether or not SGLT2 can affect the microbiota in the human gut. This trial is a pragmatic, randomized, open-label controlled study with empagliflozin as an intervention. We will enroll 100 patients with HFpEF and randomly assign them to one of two groups to receive either empagliflozin or a placebo. Patients in the Empagliflozin group will be given 10 mg of the drug daily, while those in the Control group will not be given empagliflozin or any other SGLT2. The purpose of the trial is to validate the changes that occur in gut microbiota in patients with HFpEF who take empagliflozin and to investigate the function of gut microbiota and their metabolites in the process.Keywords: derived metabolite, gut microbiota, heart failure, HF, myocardial fibrosis, SGLT2, short-chain fatty acids, SCFAs, sodium-glucose cotransporter-2 inhibitor